Stress Management Throught Cognitive Behavior Therapy Approach - Dea Aulia; Netrawati Netrawati; Yeni Karneli (Lentera Negeri, 2021)
Stress is a pressure if left unchecked will become a disease that can hinder the activities of daily life. Stress is a common thing that is often experienced by a person. But stress will also be something that is dangerous if someone can't manage it. For this reason, the purpose of this study is to manage stress through a cognitive behavior therapy approach in group counseling. To discuss these objectives, this research uses a descriptive narrative approach from the study of literature. The results of this study are that there is special training in stress management with a cognitive behavior therapy approach, namely stress meinchenbeum inoculation training using three techniques, namely (1) eliciting thoughts, feelings, and client interpretations of events; (2) gather evidence with the client to support or refute this interpretation; and (3) designing homework to test the validity of interpretations and collect more data for discussion.